Factors Influencing Adoption of Green Practices by Small and Medium Sized Hotels in Thailand - Sruangporn Satchapappichit; Noor Azmi Hashim; Zolkafli Hussin (Journal of Business Management and Accounting, 2013)
This article investigates factors that influence hotel owner-managers’ perception toward green practice adoption in Southern Thailand. The driving factors in research consisted of owner-manager attitudes, environmental awareness, perceived benefits, green consumers, and competitors. A quantitative research design was employed in conducting this study. A total of 236 questionnaires were distributed to hotels ranging from mid-scale hotels to budget hotels. A sample of 145 hotel owner-managers completed questionnaires, which were used for the analysis. This study found that owner-manager attitudes, environmental awareness, and competitors have significantly influenced the adoption of green practices. However, the effect of perceived benefits and green consumers is not significant. This article provides practical implications for small and medium sized hotels (SMHs) to adopt more green practices.